2020
DOI: 10.1093/eurpub/ckaa194
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of inequalities in years with disability: an international-comparative study

Abstract: Background Persons with a lower socioeconomic position spend more years with disability, despite their shorter life expectancy, but it is unknown what the important determinants are. This study aimed to quantify the contribution to educational inequalities in years with disability of eight risk factors: father’s manual occupation, low income, few social contacts, smoking, high alcohol consumption, high body-weight, low physical exercise and low fruit and vegetable consumption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…We found that low education, smoking, obesity and not exercising were independently associated with an increased relative risk of transitioning to disability or to death among women in both cohorts. Research suggests that people with lower education levels are likely to have unhealthy lifestyle factors, which increase their likelihood of experiencing negative health outcomes [ 20 , 36 ]. Smoking, a prevalent modifiable factor among low-educated people [ 39 ], is associated with a significant loss of years of life [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that low education, smoking, obesity and not exercising were independently associated with an increased relative risk of transitioning to disability or to death among women in both cohorts. Research suggests that people with lower education levels are likely to have unhealthy lifestyle factors, which increase their likelihood of experiencing negative health outcomes [ 20 , 36 ]. Smoking, a prevalent modifiable factor among low-educated people [ 39 ], is associated with a significant loss of years of life [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A US-based study reported that less than 12 years of schooling is associated with an increased prevalence of disability and decreased HLE or DFLE [ 19 ]. An international comparative study across 15 European countries reports that risk factors are more prevalent among low-educated women, and they had higher life with disability than those had high education, with a difference of 5.5 years [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several of the risk factors that contribute to ID could be prevented by providing quality healthcare services during pregnancy, delivery and soon after birth to mothers and children (Sutherland et al ., 2012 ). In addition, healthcare services are known to vary according to the individual-level per-capita income and country-level socio-economic position as measured using highest attained education (Stolk et al ., 2016 ; Nusselder et al ., 2021 ). As these healthcare needs may not be adequately met in several countries, primary studies on the distribution of ID and their meta-analyses indicate an increasing trend of prevalence of ID in low- and middle-income countries compared to high-income nations (Carulla et al ., 2011 ; Maulik et al ., 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies that examined factors related to the development of various disabilities, except for war, terrorism, and traffic accidents, include original studies ( 6 52 ) and meta-analyses and review research ( 53 57 ). Most studies have investigated the socioeconomic characteristics [e.g., income level, ( 8 , 9 , 14 , 17 , 20 ) and education level ( 8 , 14 , 17 , 18 , 20 )] of the population and the development of disability with respect to specific age and status [e.g., children, ( 10 , 20 ) young and middle-aged adults, ( 14 , 16 , 19 , 26 , 42 , 48 , 50 ) veterans ( 35 ), and seniors and the older adults ( 6 – 8 , 11 , 17 , 18 , 22 , 25 , 28 , 31 , 32 , 34 , 39 )]. Furthermore, many studies have identified that certain chronic diseases like hypertension, hyperlipidemia, joint, kidney and diseases [e.g., hypertension, ( 8 , 19 , 22 , 30 , 41 , 43 ) hyperlipidemia ( 19 ), diabetes, ( 8 , 30 , 35 , 36 , 40 , 41 , 51 , 55 , 57 ) cerebrovascular disease ( 18 , 30 , 51 ), respiratory and lung disease ( 15 , 30 , 43 , 45 , 50 , 57 ), cardiovascular disease ( 11 ...…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have identified that certain chronic diseases like hypertension, hyperlipidemia, joint, kidney and diseases [e.g., hypertension, ( 8 , 19 , 22 , 30 , 41 , 43 ) hyperlipidemia ( 19 ), diabetes, ( 8 , 30 , 35 , 36 , 40 , 41 , 51 , 55 , 57 ) cerebrovascular disease ( 18 , 30 , 51 ), respiratory and lung disease ( 15 , 30 , 43 , 45 , 50 , 57 ), cardiovascular disease ( 11 13 , 30 , 32 , 45 , 57 ), heart disease ( 35 , 41 , 46 , 51 ), hip joint disease ( 30 , 58 ), tuberculosis ( 54 ), kidney disease ( 44 ), HIV ( 14 ), cancer ( 30 , 41 , 57 ), and BMI/obesity ( 9 , 19 , 21 , 22 , 26 , 27 , 29 , 32 , 36 , 39 , 41 , 45 ), etc.] or health-related factors, behaviors and choices [e.g., level of physical activity ( 6 9 , 16 , 27 , 28 , 31 34 , 38 , 42 , 44 , 56 ), smoking ( 9 , 19 ,…”
Section: Introductionmentioning
confidence: 99%